Effect of far infrared and far infrared combined with hot air drying on the drying kinetics, bioactives, aromas, physicochemical qualities of Anoectochilus roxburghii (Wall.) Lindl. (1st June 2022) - Xu, Wanxiu; Pei, Yongsheng; Zhu, Guanyu; Han, Congying; Wu, Mei; Wang, Tao; Cao, Xiaohuang; Jiang, Yonghua; Li, Gang; Sun, Jianfeng; Tian, Jinghong; Tang, Chao; et al.
Abstract: Strategies of far infrared drying (FID) and far infrared combined with hot air drying (FIHAD) were employed to preserve the quality of Anoectochilus. It was dried with four different drying temperatures (50, 60, 70 and 80 °C) under FID and three different drying temperatures (50, 60, and 70 °C) under FIHAD. After drying, drying kinetics, color, and aroma of the Anoectochilus were investigated. Results showed that FIHAD strategy decreased drying time in Anoectochilus processing; it also retained better color, aroma and bioactive compound than FID. Optimal quality of samples arised from FIHAD60 °C strategy which retained better product quality. Optimal model of the Modified Henderson & Pabis was determined to predict the drying behaviour within the experimental range; it possessed with the highest R 2, lowest R M S E and χ 2 . In this work, FIHAD strategy was superior to other FID drying Anoectochilus. Highlights: FID and FIHAD were investigated to obtain the good quality of Anoectochilus. The Modified Henderson & Pabis model could precisely describe the drying kinetics. FIHAD60 °C is suggested optimum strategy in drying Anoectochilus.